Culture of rhizoidal tubers on an aquatic moss in the lakes near the Syowa Station area, Antarctica - Imura, Satoshi; Higuchi, Masanobu; Kanda, Hiroshi; Iwatsuki, Zennoske (National Institute of Polar Research, 1992)
P(論文) The rhizoidal tubers of a moss collected from the bottom of the lakes in the Syowa Station area, Continental Antarctica, were cultured Protonemata and leafy plants were developed from the tubers stored in a freezer for about two years Anthendia and archegoma were formed in the same inflorescence at the tip of the plants The morphological characters and the synoicous sexual condition of the plants agree closely with those of Leptobryum pyriforme (Hedw) Wils. departmental bulletin paper